From status quo power to reform engine: Germany's future role in the European Union - Ronja Kempin; Nicolai von Ondarza (Stiftung Wissenschaft und Politik (SWP), 2022)
One of the self-imposed goals of Germany's new Federal Government is to shift the priority of its European policy from a focus on European Union (EU) cohesion towards its reform and deepening. The first window of opportunity for this will open as early as spring 2022. In order to achieve the desired reform of the EU, however, Germany must change four aspects of its approach to European policy. It must strike a new balance between crisis mode and reform agenda; combine the community method with differentiated integration; engage in more active intra-European diplomacy to forge a reform coalition; and create concrete initiatives to operationalise the ambition for European sovereignty.
Keywords: 320